2010
DOI: 10.1021/es101313y
|View full text |Cite
|
Sign up to set email alerts
|

Emission Factors of Particulate Matter and Elemental Carbon for Crop Residues and Coals Burned in Typical Household Stoves in China

Abstract: Both particulate matter (PM) and black carbon (BC) impact climate change and human health. Uncertainties in emission inventories of PM and BC are partially due to large variation of measured emission factors (EFs) and lack of EFs from developing countries. Although there is a debate whether thermal-optically measured elemental carbon (EC) may be referred to as BC, EC are often treated as the same mass of BC. In this study, EFs of PM (EFPM) and EC (EFEC) for 9 crop residues and 5 coals were measured in actual r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
219
4
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 233 publications
(246 citation statements)
references
References 39 publications
21
219
4
2
Order By: Relevance
“…If take no account of the impact of coal maturity, EF PM measured in the present study shows a high comparability with previous measurement results. For example, Shen et al suggested a mean EF PM value of 3.17 ± 4.67 g/kg for five coals in typical household stoves (Shen et al, 2010), close to the total average of 3.69 ± 2.48 g/kg for all combinations in this experiment.…”
Section: Emission Factors Of Pm 25 and Tcsupporting
confidence: 73%
See 2 more Smart Citations
“…If take no account of the impact of coal maturity, EF PM measured in the present study shows a high comparability with previous measurement results. For example, Shen et al suggested a mean EF PM value of 3.17 ± 4.67 g/kg for five coals in typical household stoves (Shen et al, 2010), close to the total average of 3.69 ± 2.48 g/kg for all combinations in this experiment.…”
Section: Emission Factors Of Pm 25 and Tcsupporting
confidence: 73%
“…As shown in Table S2, the present EF values are somewhat lower than previous measurement results by our group and Zhang et al (Chen et al, 2005(Chen et al, , 2006Zhang et al, 2008;Zhi et al, 2008) but higher than those by Shen et al (Shen et al, 2010). The main reason may point to the different selection of coal types and stove conditions, which suggests that much more measurements need to be conducted by considering all kinds of typical coal/stove combinations, especially those actually used in rural kitchens (Shen et al, 2013b).…”
Section: Emission Factors Of Oc and Eccontrasting
confidence: 68%
See 1 more Smart Citation
“…Also, it is important to note that although our results indicate that the proportion of solid-fuel users decreased from 1991 to 2012, since the overall population in China increased significantly (from 1.16 billion in 1991 to 1.35 billion in 2012), the absolute number of people using solid fuels was still extremely large (Table S2). This suggests that a significant number of people are potentially exposed to harmful pollutants, and consequently at high risk for the development of disease, as inefficient burning of solid fuels often yield a large number of incomplete pollutants [18][19][20].…”
Section: Hfu For Cooking and Temporal-spatial Distributionmentioning
confidence: 99%
“…Compared with other locally measured results [35,36] and emission factors from foreign studies [19], Chen et al's results were adapted and used in this work. Li et al [37] obtained emission factors for crop residues and firewood for typical rural areas in China, and Shen et al [38] and Cao et al [39] developed crop residue emission factors using actual and simulative stoves. The emission factors for biofuels in our work were deduced from the above researches; for example, the geometric mean of the three factors named above was used as the emission factor of crop residues.…”
Section: Emission Factorsmentioning
confidence: 99%